(untitled) (Asian Journal of Pharmaceutics (AJP), 2015)
To explore opinions of pharmacist toward pharmaceutical care (PC) in Riyadh, the capital of Saudi Arabia. A descriptive, cross-sectional survey was conducted over a 3 months period (November 2012 to January 2013) in National Guard Primary Health Center, Riyadh the capital of Saudi Arabia. A 20-item questionnaire was adopted, validated and given to 100 pharmacists. The response rate was 80% where 100 respondents were approached, and 80 of them responded to our survey questionnaire. Overall Pharmacists expressed positive attitudes toward PC. A total of 73 (91%) respondents indicated that common situation regarding appropriateness of prescribing was receiving an error in prescription with incomplete information. A majority of the respondents (78.6%) disagreed or strongly disagree with the statement, that pharmacist of primary healthcare centers have insufficient knowledge/ skills to provide PC. The finding of this study revealed that pharmacists have positive attitudes toward PC overall. More attention should be given to improve pharmacists’ actual PC capabilities to extend their professional role. However, new development in Saudi hospitals would be recommended to improve health care systems.